The Influence of Social-Media on Cultural Integration: A Perspective on Digital Sociology - Guntur Arie Wibowo; Hanna; Faria Ruhana; Farida M. Arif; Usmaedi (International Journal of Science and Society, 2023)
Technological developments have made social media a part of people's daily lives. The ability of social media to cross geographical boundaries causes a culture change, especially in cultural integration. This research then aims to look at the role of social media in influencing cultural interactions in society. This research will be carried out using a descriptive qualitative approach. The data used in this research comes from various research results and previous studies that are still relevant. The results of this research then show that the presence of social media makes cultural integration more complicated. The presence of social media plays a key role but also provides new challenges in society. Therefore, the importance of wise use of social media in cultural integration is very necessary. To achieve deeper cultural integration, efforts need to be made to minimize risks such as filter bubbles, polarization, and cultural conflicts that can arise in the digital world.